(untitled) (KULT_online, 2021)
The educationalist Lilli Riettiens presents an impressive synthesis of theoretical explanations and empirical analysis of historical travelogues with her monograph. Through the analysis of Spanish travelogues that deal with the Atlantic crossings from Latin America to Europe in the nineteenth century, she explores – guided by historical praxeology – practices of departure, the crossing and arrival as well as the writing of the travelogues.